Accurate and selective quantification of anthrax protective antigen in plasma by immunocapture and isotope dilution mass spectrometry. Issue 7 (27th February 2019) - Solano, Maria I.; Woolfitt, Adrian R.; Boyer, Anne E.; Lins, Renato C.; Isbell, Katie; Gallegos-Candela, Maribel; Moura, Hercules; Pierce, Carrie L.; Barr, John R.
Abstract : The impact of anthrax PA levels during anthrax infections can be assessed by a novel Ab-capture, tryptic digest LC-MS/MS method. Abstract : Anthrax protective antigen (83 kDa, PA83) is an essential component of two major binary toxins produced by Bacillus anthracis, lethal toxin (LTx) and edema toxin (ETx). During infection, LTx and ETx contribute to immune collapse, endothelial dysfunction, hemorrhage and high mortality. Following protease cleavage on cell receptors or in circulation, the 20 kDa (PA20) N-terminus is released, activating the 63 kDa (PA63) form which binds lethal factor (LF) and edema factor (EF), facilitating their entry into their cellular targets. Several ELISA-based PA methods previously developed are primarily qualitative or semi-quantitative. Here, we combined protein immunocapture, tryptic digestion and isotope dilution liquid chromatography-mass spectrometry (LC-MS/MS), to develop a highly selective and sensitive method for detection and accurate quantification of total-PA (PA83 + PA63) and PA83. Two tryptic peptides in the 63 kDa region measure total-PA and three in the 20 kDa region measure PA83 alone. Detection limits range from 1.3–2.9 ng mL −1 PA in 100 μL of plasma. Spiked recovery experiments with combinations of PA83, PA63, LF and EF in plasma showed that PA63 and PA83 were quantified accurately against the PA83 standard and that LF and EF did not interfere with accuracy. Applied to a study of inhalation anthrax in rhesus macaques, total-PA suggested triphasic kinetics, similar to that previously observed for LF and EF. This study is the first to report circulating PA83 in inhalation anthrax, typically at less than 4% of the levels of PA63, providing the first evidence that activated PA63 is the primary form of PA throughout infection.